Elevated expression of the metalloproteinase ADAM8 associates with vascular diseases in mice and humans. (July 2019) - Schick, Daniel; Babendreyer, Aaron; Wozniak, Justyna; Awan, Tanzeela; Noels, Heidi; Liehn, Elisa; Bartsch, Jörg-W.; Vlacil, Ann-Kathrin; Grote, Karsten; Zayat, Rashad; Goetzenich, Andreas; Ludwig, Andreas; et al.
Abstract: Background and aims: Members of the family of a disintegrin and metalloproteinases (ADAMs) and their substrates have been previously shown to modulate the inflammatory response in cardiac diseases, but studies investigating the relevance of ADAM8 are still rare. Our aim is to provide evidence for the inflammatory dysregulation of ADAM8 in vascular diseases and its association with disease severity. Methods: Western-type diet fed Apoe −/− and Ldlr −/− mice and artery ligation served as murine model for atherosclerosis and myocardial infarction, respectively. Human bypass grafts were used to study the association with coronary artery disease (CAD), with the simplified acute physiology score II (SAPS II) as a measure of postoperative organ dysfunction. Human primary vascular and blood cells were analyzed under basal and inflammatory conditions. mRNA levels were determined by RT-qPCR, ADAM8 protein levels by ELISA, immunohistochemistry or flow cytometry. Results: ADAM8 /ADAM8 expression is associated with atherosclerosis and CAD such as myocardial infarction in both mice and humans, especially in endothelial cells and leukocytes. We observed a strong in vivo and in vitro correlation of ADAM8 with the vascular disease markers VCAM-1, ICAM-1, TNF, IL-6, and CCL-2 . Serum analysis revealed a significant elevation of soluble ADAM8 serum levels correlating with soluble CXCL16 levels and SAPS II. Conclusions: We demonstrate a general association of ADAM8 with cardiovascular diseases in mice and humans predominantly acting in endothelial cells and leukocytes. The correlation with postoperative organ dysfunctions in CAD patients highlights the value of further studies investigating the specific function of ADAM8 in cardiovascular diseases. Graphical abstract: Image 1 Highlights: ADAM8 associates with cardiovascular diseases in both mice and humans. ADAM8 associates with vascular disease markers. Soluble ADAM8 serum levels correlate with postoperative organ dysfunction.